Implication for media convergence on news learning - Gümüş, Agah; Özad, Bahire Efe (My University, 2011)
Over the last decade, comparisons of the effects of the traditional news media and the Internet have been made in relation to comprehension and remembering,. This study aims at assessing the effects of single and compound presentational elements, and making predictions for the future. One of the two main aims of this study is to measure comprehension and remembering effect of the traditional media instruments and the Internet. It includes a comparison of the media instruments and the Internet in order to find out the most effective media instrument for comprehension and remembering. The second aim of this study, after finding the most effective media instrument, is to find the preferences of the user of these instruments in terms of the presentational formats. The results of this study indicate that comprehension and remembering are not due to the individual effects of a stimulus, but rather an increase in the quantity of stimuli also increases the preference of users. When users are exposed to multiple stimuli, they select the dual-stimuli format with which they feel most comfortable, or they are most familiar. © The Turkish Online Journal of Educational Technology.
Keywords: Comprehension; Convergence; Learning; Media effect; Remembering